Depression in the Direct Pathway of the Dorsomedial Striatum Permits the Formation of Habitual Action. (29th March 2021) - Yu, Xiaoxuan; Chen, Shijie; Shan, Qiang
Abstract: In order to achieve optimal outcomes in an ever-changing environment, humans and animals generally manage their action control via either goal-directed action or habitual action. These two action strategies are thought to be encoded in distinct parallel circuits in the dorsal striatum, specifically, the posterior dorsomedial striatum (DMS) and the dorsolateral striatum (DLS), respectively. The striatum is primarily composed of two subtypes of medium spiny neurons (MSNs): the direct-pathway striatonigral and the indirect-pathway striatopallidal MSNs. MSN-subtype-specific synaptic plasticity in the DMS and the DLS has been revealed to underlie goal-directed action and habitual action, respectively. However, whether any MSN-subtype-specific synaptic plasticity in the DMS is associated with habitual action, and if so, whether the synaptic plasticity affects the formation of habitual action, are not known. This study demonstrates that postsynaptic depression in the excitatory synapses of the direct-pathway striatonigral MSNs in the DMS is formed after habit learning. Moreover, chemogenetically rescuing this depression compromises the acquisition, but not the expression, of habitual action. These findings reveal that an MSN-subtype-specific synaptic plasticity in the DMS affects habitual action and suggest that plasticity in the DMS as well as in the DLS contributes to the formation of habitual action.